Comparison of post-endodontic restoration preferences among dental specialists and general dental practitioners: a cross-sectional web-based survey - NALCI ÇALIK G.; Alim Uysal B. A. (My University, 2025)
Purpose: The quality and type of coronal restoration are critical determinants of the long-term survival of endodontically treated teeth. Differences in clinical training and professional experience may influence restoration preferences among dental specialists and general dental practitioners. This study aimed to compare post-endodontic restoration choices for mandibular first molars among endodontists, restorative dentistry specialists, prosthodontists, and general dental practitioners. Methods: A web-based survey presenting six standardized clinical scenarios of endodontically treated mandibular first molars was distributed to 1,369 dentists across various institutions. The participants selected among seven treatment options for each case and were asked to indicate their preferred method of restoration for each tooth. A chi-squared test was used to determine the relationship between specialty, years in practice, institution, sex, and treatment choices (p < 0.05). Results: A total of 764 dentists completed the survey, yielding a 55.8% response rate. Responses differed significantly between specialties for all cases. Prosthodontists and restorative specialists favored inlay/onlay/overlay restorations, while general dental practitioners and endodontists preferred composites for the Black’s class II mesio-occlusal cavity (Case 1) and the Black’s class II mesio-occlusal-distal cavity (Case 2) (p < 0.001). In Case 3, general dental practitioners mostly chose post–crown restorations, whereas prosthodontists preferred endocrowns (p < 0.001). for the hole cavity 2 mm above the cementoenamel junction (CEJ) (Case 4) (p < 0.001) and the scenario involving a hole cavity at the CEJ (Case 5) (p = 0.041), post–crown restorations were more frequently selected by general dental practitioners. In the cavity without a buccal wall (Case 6), post–crown restorations were the dominant choice across all groups, though proportions varied significantly by specialty (p = 0.033). Conclusions: Specialty and practice setting significantly influence post-endodontic restoration choices. These findings underscore the need for updated, cross-specialty guidelines and enhanced educational strategies to improve consistency in clinical decision-making.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Diş Hekimliği Oral Cerrahi ve Tıp; Klinik Tıp (Med); Klinik Tıp; Dentistry Oral Surgery & Medicine; Clinical Medicine (Med); Clinical Medicine; General Dentistry; Coronal restoration; Decision making; Endodontist; Post-endodontic treatment; Prosthodontist